If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + 1 = 1 + -6y + -10 Reorder the terms: 1 + -4y = 1 + -6y + -10 Reorder the terms: 1 + -4y = 1 + -10 + -6y Combine like terms: 1 + -10 = -9 1 + -4y = -9 + -6y Solving 1 + -4y = -9 + -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. 1 + -4y + 6y = -9 + -6y + 6y Combine like terms: -4y + 6y = 2y 1 + 2y = -9 + -6y + 6y Combine like terms: -6y + 6y = 0 1 + 2y = -9 + 0 1 + 2y = -9 Add '-1' to each side of the equation. 1 + -1 + 2y = -9 + -1 Combine like terms: 1 + -1 = 0 0 + 2y = -9 + -1 2y = -9 + -1 Combine like terms: -9 + -1 = -10 2y = -10 Divide each side by '2'. y = -5 Simplifying y = -5
| 3/8x-1/2=21/8 | | s(s/3/5)=-3/7 | | -24=5x-8x | | -6p-9=3p | | 2b+1=18 | | -7+4z=2z+7 | | y-2=-7/8(x-8) | | -7+4f=2z+7 | | -9-u=-4u | | -14+34=6x-56 | | 6x+12=-6x-17 | | Y=-3*(3*3)-1 | | 6x+12=6x-17 | | -3+7f=8f+4 | | -13+6y= | | -csc(3.14/4) | | 2sec^2=0 | | 4x+15=-9x-17 | | Y=-3*(-3*-3)-1 | | 2x-30=5x-10 | | 4(x+4)=4(x+9) | | tan^4x-5tan^2x+4=0 | | 10x+15=6-2x+3 | | 40x+12(2x)=544 | | 2x+2y=2z | | 74(5x)= | | 2f(5)=25-11 | | 4(-5-5n)+3n=82 | | 10-y=3y-10 | | 17x^2-84x+99=0 | | 4(-5-5n)+3= | | 9z-3=-7+8z |